2012
DOI: 10.1007/s13320-012-0073-4
|View full text |Cite
|
Sign up to set email alerts
|

Light enhancement in surface-enhanced Raman scattering at oblique incidence

Abstract: Surface enhanced Raman scattering (SERS) measurements have been carried out at different focusing conditions using objective lenses of different numerical apertures. The experimentally observed dependence of SERS intensity of thiophenol-coated Ag nano-islands shows a close-to-linear scaling with the collection aperture. The linear relationship breaks down for large numerical apertures, which suggests that the scattering is anisotropic. Numerical simulations of realistically shaped Ag nano-islands were carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 12 publications
(12 reference statements)
3
19
0
Order By: Relevance
“…Note that there is considerable evidence that the SERS signal tends to be dominated by scattering from hot spots such as the nanogap considered in this model2425. Recent FDTD modeling has confirmed that this assumption remains valid for the case of silver island films formed by oblique island deposition10.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Note that there is considerable evidence that the SERS signal tends to be dominated by scattering from hot spots such as the nanogap considered in this model2425. Recent FDTD modeling has confirmed that this assumption remains valid for the case of silver island films formed by oblique island deposition10.…”
Section: Resultsmentioning
confidence: 58%
“…Higher NA objectives will tend to introduce a perpendicular polarization component with respect to the dielectric surface. This polarization will not be effective in exciting hot spots between neighboring metal particles, thus causing a decrease in the average SERS intensity10. This effect may be further exaggerated due to diffraction in the far-side excitation geometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also observed that the s polarised light gave greater Raman intensities, a result that was consistent with the FDTD calculations. FDTD has also been used to investigate the anisotropic effects of using different objectives and apatures for SERS measurements [45]. Here, the linear relationship of larger apature with Raman intensity was observed to breakdown for large (solid angle > 1) numerical apatures.…”
Section: Finite Difference Time Domainmentioning
confidence: 92%
“…This requires a very accurate fabrication capability in order to control the particle layout and shape in ordered or semi-random patterns, as has been shown in several instances in light harvesting and sensing applications, [3][4][5][6] and in the development of light-driven nano-motors. 7 When such tiny objects are in close proximity of metal edges and grooves, especially of regions where field enhancement hot-spots are located, they selectively interact with the light near-field increasing or reducing the trapping force.…”
Section: Introductionmentioning
confidence: 99%